2022
DOI: 10.1590/s2175-97902022e19587
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of analytical methods by HPLC for quality control of avermectins and milbemycins in bulk samples

Abstract: This work aims to develop analytical methods using high-performance liquid chromatography with a diode array detector (HPLC-DAD) for analysis and quantification of avermectins (AVMs) and milbemycins (MBMs) in bulk samples. First, the methods were optimized and some parameters such as temperature, flow rate, injection volume and mobile phase with different proportions of solvents were evaluated. The best chromatographic conditions were obtained using the Phenomenex ® C18 (150 × 4.60 mm, 5 μm) column at a temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The chromatographic analyses were performed using an HPLC system [27][28][29][30] model Alliance 2696 (Waters ® , Wexford, Ireland), equipped with a C18 reversed phase column (4.6 x 75mm, 3.5µm) (Symmetry Waters ® , Wexford, Ireland), a photodiode array detector (Waters ® , Wexford, Ireland) and the Empower 3 ® software (Waters ® , Milford, MA, USA). The study was performed using isocratic elution of mobile phase comprised of acetonitrile:methanol:water (47:33:20, v/v/v), flow of 1.5 mL/min, and at the temperature of 30 ºC.…”
Section: Instrumentation and Chromatographic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatographic analyses were performed using an HPLC system [27][28][29][30] model Alliance 2696 (Waters ® , Wexford, Ireland), equipped with a C18 reversed phase column (4.6 x 75mm, 3.5µm) (Symmetry Waters ® , Wexford, Ireland), a photodiode array detector (Waters ® , Wexford, Ireland) and the Empower 3 ® software (Waters ® , Milford, MA, USA). The study was performed using isocratic elution of mobile phase comprised of acetonitrile:methanol:water (47:33:20, v/v/v), flow of 1.5 mL/min, and at the temperature of 30 ºC.…”
Section: Instrumentation and Chromatographic Conditionsmentioning
confidence: 99%
“…However, no study reported the application of the method for quantification of the active in a polymeric system (containing Poloxamer P407, Carbopol C974P and isopropanol) for veterinary use. Most studies are applied to detection in milk [27,28]. Therefore, the aim of this work was to develop and validate a high-performance liquid chromatographic (HPLC) method for analysis of EPR from the polymeric systems.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular weight is 435.89 g/mol, and its IUPAC nomenclature is 5-chloro-N-[(5S) [4-(3oxomorpholin -4-yl) phenyl]-2-oxo-3-Thiophene-2carboxamide, or [-1, 3-oxazolidin-5-yl]methylthiophene [1][2][3]. It belongs to a class of an anticoagulant [4]. It is used in the treatment of deep venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%